2003
DOI: 10.1007/s11746-003-0742-9
|View full text |Cite
|
Sign up to set email alerts
|

Tocol levels in milling fractions of some cereal grains and soybean

Abstract: Tocol levels in the milling fractions of rice, barley, corn, wheat, and soybeans were analyzed by HPLC with a fluorescence detector. Among all milling fractions tested in this study, rice germ had the highest total tocol levels. In the four milling fractions of barley, except pearling flour, all eight tocol isomers were detected, and they were more uniformly distributed than in any other cereal grains measured in this study. The total tocol and α-tocopherol levels of wheat germ were significantly (P < 0.05) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 13 publications
4
21
0
1
Order By: Relevance
“…isomers, a-(21), c-(23), and d-tocotrienol (24), were detected but no b-tocotrienol (22) was detectable in this study. This result was similar to that in rice bran lipid extract as reported by Ko et al (2003). A marked decrease in the total tocopherol (17-20) level was observed while the total tocotrienol (21, 23, 24) level steadily increased during rice seed development.…”
Section: Tocol (17-24) Levels In Whole Rice Seed Lipid Extractsupporting
confidence: 90%
“…isomers, a-(21), c-(23), and d-tocotrienol (24), were detected but no b-tocotrienol (22) was detectable in this study. This result was similar to that in rice bran lipid extract as reported by Ko et al (2003). A marked decrease in the total tocopherol (17-20) level was observed while the total tocotrienol (21, 23, 24) level steadily increased during rice seed development.…”
Section: Tocol (17-24) Levels In Whole Rice Seed Lipid Extractsupporting
confidence: 90%
“…These phytochemicals are known to be synthesized in the bran and germ, which accounts for approximately 7% by weight of the whole grain (i.e., including the hull) at maturity (Ko et al 2003). These phytochemicals are known to be synthesized in the bran and germ, which accounts for approximately 7% by weight of the whole grain (i.e., including the hull) at maturity (Ko et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The present study adds to our understanding of the biosynthetic pathways of the tocopherols, tocotrienols, and g-oryzanol and the concentration of these compounds found during kernel development. These phytochemicals are known to be synthesized in the bran and germ, which accounts for approximately 7% by weight of the whole grain (i.e., including the hull) at maturity (Ko et al 2003). In the present study, the starch concentration in the endosperm was low at early developmental stages and accumulated rapidly from the milky to soft dough stages.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that the bran and feed (middlings and tailings) fractions of wheat have the highest antioxidant capacity, followed by shorts and flour fractions, but that the germ fraction has the highest concentration of α-T (Ko et al 2003;Liyana-Pathirana and Shahidi 2007). The higher content of tocotrienols in the bran fractions might contribute to the higher antioxidant properties of these fractions.…”
Section: Distribution Of Vitamin E In Mill Streamsmentioning
confidence: 97%
“…Because wheat is normally used as straight-grade flour or patent flour without bran and germ fractions, only few studies have been made to investigate the content of vitamin E in different fractions from wheat milling. The total vitamin E content of several products includes wheat germ oil 3,121 µg/g; wheat germ 152-252 µg/g; wheat bran 14-75 µg/g; whole meal flour 76 µg/g, and white wheat flour 9-32 µg/g (Barnes and Taylor 1980;Morrison et al 1982;Piironen et al 1986;Håkansson and Jägerstad 1990;Wennermark and Jagerstad 1992;Ko et al 2003;Leenhardt et al 2006). The distribution of the different isomers of vitamin E has hardly been investigated in different milling fractions of wheat.…”
mentioning
confidence: 99%